1961
DOI: 10.1152/ajplegacy.1961.200.5.1099
|View full text |Cite
|
Sign up to set email alerts
|

Calcium clearance as a function of sodium clearance in the dog

Abstract: During diuresis induced in dogs by water, sodium chloride, sodium bicarbonate, mannitol, glucose, or sucrose, the plasma calcium clearance is, on the average, half the sodium clearance. Free calcium ion clearance therefore equals sodium clearance. This relationship is not altered by reducing calcium or sodium intake, by varying urinary flow or urinary ionic strength, or by varying chloride excretion, independently of sodium excretion. It is only slightly affected by urinary pH, and is not distinctly altered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
0
5

Year Published

1965
1965
1992
1992

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(86 citation statements)
references
References 0 publications
7
74
0
5
Order By: Relevance
“…For example, in clearance and micropuncture experiments in rabbits by Chonko et al (36), the J, rate in the proximal convoluted tubule was 1.9 nl/mm * min. However, most studies of J, in the proximal tubule in vitro find 50% of this rate, i.e., 0.8-1.0 nl/mm * min (15,18,33,37 The finding of passive calcium transport in the S2 segment of the superficial proximal convoluted tubule of the rabbit is consonant with the published literature that suggests that there is an interdependence of sodium and calcium (38,39). Those maneuvers, which depress proximal tubular reabsorption of sodium and water, such as volume expansion (38), PTH, (40), insulin (41), renal vasodilators (42), and acetazolamide (43), also similarly depress proximal tubular reabsorption of calcium, which results in parallel excretion of sodium and calcium in the final urine.…”
Section: Discussionsupporting
confidence: 77%
“…For example, in clearance and micropuncture experiments in rabbits by Chonko et al (36), the J, rate in the proximal convoluted tubule was 1.9 nl/mm * min. However, most studies of J, in the proximal tubule in vitro find 50% of this rate, i.e., 0.8-1.0 nl/mm * min (15,18,33,37 The finding of passive calcium transport in the S2 segment of the superficial proximal convoluted tubule of the rabbit is consonant with the published literature that suggests that there is an interdependence of sodium and calcium (38,39). Those maneuvers, which depress proximal tubular reabsorption of sodium and water, such as volume expansion (38), PTH, (40), insulin (41), renal vasodilators (42), and acetazolamide (43), also similarly depress proximal tubular reabsorption of calcium, which results in parallel excretion of sodium and calcium in the final urine.…”
Section: Discussionsupporting
confidence: 77%
“…The renal tubular reabsorption of calcium is closely related to that of sodium (17,18,20,21), and it is likely that certain events promoting sodium transport in the nephron can also augment the reabsorption of calcium. Also, enhanced tubular reabsorption of calcium follows increased action of parathyroid hormone (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Walser pointed out that the natriuresis induced by mercurial diuretics and acetazoleamide is accompanied by a simultaneous increase in urinary calcium excretion and suggested that the transport of these ions in the kidney is related, with a common transport mechanism possibly being involved. 12 Walser also noted that the diuretics of the benzothiadiazine class have the opposite effect but offered no explanation for this. '3 The reduction in calcium clearance induced by the thiazides could be due to a fall in the filtered calcium load resulting either from diminished glomerular filtration rates, or from increased protein binding of plasma calciumn.…”
Section: Resultsmentioning
confidence: 99%